Angsuran PPH pasal 25 setelah berakhirnya penerapan PP 23 tahun 2018 pada UMKM - Soerjatno, Raden (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Government Regulation Number 23 of 2018 which came into effect on July 1, 2018 which allows Micro, Small and Medium Enterprises (MSMEs) to calculate their Income Tax easily, namely by multiplying the tariff by 0.5% of Gross Circulation and is final, meaning that it is no longer available. Whatever the next tax calculation, this is intended so that Micro, Small and Medium Enterprises actors are not burdened with complicated tax calculations and the tax rate is also not too heavy because it is only 0.5%. Income Tax calculation based on Government Regulation Number 23 of 2018 for each Taxpayer has a time limit, for Limited Liability Companies 3 years, for CV, Firms and the like 4 years, and for Individuals 7 years. After the completion of the period required by Government Regulation Number 23 of 2018, Micro, Small and Medium Enterprises actors are required to re-calculate Income Tax in accordance with Article 17 of the Income Tax Law. The calculation of the installments of PPh Article 25 for the following tax year after the end of the calculation of Income Tax based on Government Regulation Number 23 of 2018 is carried out based on Article 25 and Article 17 of the Income Tax Law, as well as Circular Letter of the Director General of Taxes Number SE-46/PJ/ 2020 August 18, 2020, and Minister of Finance Regulation Number PMK.215/PMK.03/2018.